2017
DOI: 10.1016/j.fertnstert.2017.07.1163
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic expression of PGRMC1 and SERBP1 in human endometrium: an implication in the human decidualization process

Abstract: Our results suggest that classic P receptors (PRs) are not the only kind playing a role in the normal physiology of the endometrium. The human decidualization process could be altered by the overexpression or mislocalization of PGRMC1 in ESC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 53 publications
2
21
0
Order By: Relevance
“…PGRMCs are encoded by two genes, PGRMC1 and PGRMC2, and their expression was originally discovered in rat and porcine hepatocytes (77, 78). Since then, PGRMC1 has been isolated from a range of human cells and tissues, including neuronal, breast, and reproductive tissues (62, 7981), and have been found to localize to both the plasma membrane and organelle membranes (8285). The ability of PGRMC1 to bind to P4 has been demonstrated with the use of radioactive P4 ligand binding measurements from porcine liver membrane fractions and, more recently, spectroscopy (77, 86).…”
Section: Receptor-mediated Actionsmentioning
confidence: 99%
“…PGRMCs are encoded by two genes, PGRMC1 and PGRMC2, and their expression was originally discovered in rat and porcine hepatocytes (77, 78). Since then, PGRMC1 has been isolated from a range of human cells and tissues, including neuronal, breast, and reproductive tissues (62, 7981), and have been found to localize to both the plasma membrane and organelle membranes (8285). The ability of PGRMC1 to bind to P4 has been demonstrated with the use of radioactive P4 ligand binding measurements from porcine liver membrane fractions and, more recently, spectroscopy (77, 86).…”
Section: Receptor-mediated Actionsmentioning
confidence: 99%
“…This pathway could be physiologically important because many of the actions of P 4 occur too rapidly to be explained by changes in gene and/or protein expression (90). Uterine epithelial cell PGRMC1 content in macaques and humans was higher during the proliferative than the secretory phase of menstrual cycles (91,92). Ablation of Pgrmc1 from the mouse uterus reduced litter sizes 40% without affecting the ability of the animals to ovulate (90).…”
Section: Insr Mrna Expression In Response To E 2 P 4 and Insulinmentioning
confidence: 99%
“…Because PGRMC1 was predominantly found expressed in stromal cells as opposed to epithelial cells in the mid-secretory phase, it was initially presumed that it was a critical regulator of decidualization. In the past year, a more convincing study demonstrated that overexpression of PGRMC1 in stromal cells compromised in-vitro-induced decidualization as manifested by attenuated PRL synthesis and absence of typical morphological features [ 103 ]. Notably, the authors have previously discovered the PGRMC1 protein to be one of the few differentially expressed between receptive and nonreceptive endometrium [ 104 ].…”
Section: Decidualization Route: Priming the Endometrium For Implanmentioning
confidence: 99%